Differential gradients of immunotherapy vs targeted therapy efficacy according to the sun-exposure pattern of the site of occurrence of primary melanoma: a multicenter prospective cohort study (MelBase) - Russo, David; Dalle, Stéphane; Dereure, Olivier; Mortier, Laurent; Dalac-Rat, Sophie; Dutriaux, Caroline; Leccia, Marie-Thérèse; Legoupil, Delphine; Montaudié, Henri; Maubec, Eve; De Quatrebarbes, Julie; Arnault, Jean-Philippe; et al. (Frontiers in Oncology, 2023)
Background: The tumor mutational burden (TMB) is high in melanomas owing to UV-induced oncogenesis. While a high TMB is a predictive biomarker of response to PD-1 inhibitors, it may be associated with the rise of resistant clones to targeted therapy over time. We hypothesized that survivals may depend on both the sun-exposure profile of the site of primary melanoma and the type of systemic treatment. Patients and methods: Patients were screened from MelBase, a multicenter biobank dedicated to the prospective follow-up of stage III/IV melanoma. All patients with a known cutaneous primary melanoma who received a 1st-line systemic treatment by immunotherapy or targeted therapy were included (2013-2019). Outcomes were progression-free survival (PFS) and overall survival (OS). Results: 973 patients received either anti PD-1(n=466), anti CTLA-4(n=143), a combination of both (n=118), or targeted therapies (n=246). Patients’ characteristics at treatment initiation were: male (62%), median age of 62, AJCC stage IV (84%). Median follow-up was 15.5 months. The primary melanoma was located on chronically sun-exposed skin in 202 patients (G1: head neck), on intermittently sun-exposed skin in 699 patients (G2: trunk, arms, legs), and on sun-protected areas in 72 patients (G3: palms, soles). Median PFS was significantly higher in G1 under anti PD-1 treatment (8.7 months vs 3.3 and 3.4 months for G2 and G3, respectively) (p=0.011). PFS did not significantly differ in other groups. Similarly, median OS was significantly higher in G1 receiving 1st line anti PD-1 treatment (45.6 months vs 31.6 and 21.4 months for G2 and G3) (p=0.04), as opposed to 1st line targeted therapy (19.5 months vs 16.3 and 21.1 months for G1, G2 and G3 respectively). Conclusion: Our study confirms that immunotherapy with anti PD-1 is particularly recommended for melanomas originating from chronically sun-exposed areas, but this finding needs to be confirmed by further research.